Ischemia postconditioning protects dermal microvascular endothelial cells of rabbit epigastric skin flaps against apoptosis via adenosine A2a receptors. Issue 2 (4th March 2019) - Cao, Jiankun; Lin, Huang; Li, Wenzhi; Dong, Ziying; Shi, Yanyu; Zhang, Xiufang; Xiao, Ran
Abstract: Background: It has been shown that endogenous adenosine-induced by ischemia postconditioning attenuates apoptosis in recent studies; however, they focus only on parenchymal cells. The detailed mechanism has not been clearly clarified in any research and the subtype of adenosine receptors involved remains unknown. In our study, dermal microvascular endothelial cells (DMECs) are used to explore the role of adenosine A2a receptor in the anti-apoptotic effects of ischemic postconditioning. Material and methods: The epigastric skin flaps of rabbits were elevated. After 4 h of ischemia, the flaps were either abruptly reperfused or postconditioned by six cycles of brief reperfusion (15s) and re-ischemia (15s). Adenosine A2a receptor agonist (CGS-21680) and antagonist (ZM-241385) were used separately in other groups. The apoptosis-related proteins and adenosine A2a receptors were determined by immunohistochemical staining. Then apoptosis index was calculated by TUNEL. Results: Ischemia/reperfusion caused severe damages in DMECs of flaps as demonstrated by an increase in apoptosis index and an increase in expressions of apoptosis-related proteins, which can be significantly attenuated by IPC treatment or exposure to a selective adenosine A2a receptor agonist (all p values <.05). Meanwhile, the anti-apoptosis effects of IPC can be blocked by a selective adenosine A2a receptor antagonist. Statistical analysis revealed that the increase of apoptosis index closely correlated inversely with the relative increase of adenosine A2a receptors ( p < .0001). Conclusions: Ischemia postconditioning protects DMECs of rabbit skin flap against apoptosis via activation of adenosine A2a receptors.